Antonio María Mateo Gutiérrez, Reception speech of the Academic Correspondent Dr. D. Pascual González Masegosa, Royal Academy of Medicine and Surgery of Valladolid, May 18, 2019. (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
His Excellency Mr. President; Academics; Hon. Mr. Territorial Head of Culture of Valladolid; Health Authorities, Mayors of towns with bullfighting tradition in the province; Distinguished colleagues, Ladies and Gentlemen, Pere Sánchez Ferré in his novel "El Caballero del Oro Fino: Cabals y Alquimia en el Quijote"  narrates the moment in which the protagonist, the so-called Golden Knight, invites Sancho, Governor of the Barataria Island, to occupy a prominent position in his room and tells him: "I want you to feel here, by my side and in the company of these good people...". Dr. González Masegosa, Governor of the Insula in which the Spanish bullfighting surgeons live, take a seat here, at our side, in the company of these good people who have enjoyed your speech and who will now have to patiently endure mine.